Effect of LMZBS glass on the microstructure and microwave dielectric properties of monocelsian ceramics. Issue 8 (1st June 2020) - Wang, Mingxia; Zhong, Chaowei; Qin, Tianying; Yang, Qiu; Tang, Bin; Zhang, Shuren
Abstract: BaAl2 Si2 O8 –Li2 O–MgO–ZnO–B2 O3 –SiO2 (BAS-LMZBS) glass ceramics were prepared through the solid-state route. The phase transformation, microstructure, bulk density and microwave dielectric properties of (1- x )BaAl2 Si2 O8 - x LMZBS( x = 0.1–0.4) the glass ceramics were examined. The effects of the LMZBS additive as a mineralizer on the hexagonal-to-monoclinic transformation were investigated by X-ray diffraction and scanning electron microscope. All of the hexagonal phases were converted into monoclinic phases when x = 0.1, and it was found that LMZBS glass affected the densification of the ceramic samples. Monocelsian was successfully prepared, and its sintering temperature was reduced from above 1400 °C–870 °C by adding LMZBS glass. Excellent microwave dielectric properties ( ε r = 7.31, Q × f = 48, 926 GHz and τ ƒ = −48 ppm/°C) were obtained at 870 °C. This sample shows great chemical compatibility with Ag electrodes and can be a promising candidate for practical applications of low-temperature, co-fired ceramics.